Remote runtime steering of integrated terascale simulation and visualization - Tu, Tiankai; Yu, Hongfeng; Bielak, Jacobo; Ghattas, Omar; Lopez, Julio C.; Ma, Kwan-Liu; O'Hallaron, David R.; Ramirez-Guzman, Leonardo; Stone, Nathan; Taborda-Rios, Ricardo; Urbanic, John (Conference on High Performance Networking and Computing: Proceedings of the 2006 ACM/IEEE conference on Supercomputing; 11-17 Nov. 2006, 2006)
We have developed a novel analytic capability for scientists and engineers to obtain insight from ongoing large-scale parallel unstructured mesh simulations running on thousands of processors. The breakthrough is made possible by a new approach that visualizes partial differential equation (PDE) solution data simultaneously while a parallel PDE solver executes. The solution field is pipelined directly to volume rendering, which is computed in parallel using the same processors that solve the PDE equations. Because our approach avoids the bottlenecks associated with transferring and storing large volumes of output data, it offers a promising approach to overcoming the challenges of visualization of petascale simulations. The submitted video demonstrates real-time on-the-fly monitoring, interpreting, and steering from a remote laptop computer of a 1024-processor simulation of the 1994 Northridge earthquake in Southern California.